2016
DOI: 10.1002/cncr.30379
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of dasatinib in patients with alveolar soft part sarcoma, chondrosarcoma, chordoma, epithelioid sarcoma, or solitary fibrous tumor

Abstract: BACKGROUND: Alveolar soft part sarcoma (ASPS), chondrosarcoma (CS), chordoma, epithelioid sarcoma, and solitary fibrous tumor (SFT) are malignant tumors that are relatively resistant to chemotherapy and for which more effective drug therapy is needed. METHODS: The 5 listed subtypes were enrolled into a single indolent sarcoma cohort in a phase 2 study of dasatinib using a Bayesian continuous monitoring rule for enrollment. The primary objective was to estimate the 6-month progression-free survival (PFS) rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 24 publications
(66 reference statements)
2
79
0
1
Order By: Relevance
“…Furthermore, response rate is not always an indicator of sensitivity to CHT and needs to be further evaluated as the outcome of patients with MD is poor despite response to CHT of 40%. Targeted therapies are being evaluated in current clinical trials, and the first results in adults have been published . Targeted therapy was not used in the pediatric and adolescent group analyzed.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, response rate is not always an indicator of sensitivity to CHT and needs to be further evaluated as the outcome of patients with MD is poor despite response to CHT of 40%. Targeted therapies are being evaluated in current clinical trials, and the first results in adults have been published . Targeted therapy was not used in the pediatric and adolescent group analyzed.…”
Section: Discussionsupporting
confidence: 88%
“…Cediranib has also demonstrated encouraging efficacy in a phase II trial with an objective response rate of 35% and a disease control rate of 84% at 24 weeks . Also, >10% of the ASPS patients treated with dasatinib showed disease stabilization for >1 year . Finally, Azizi et al reported that bevacizumab, a monoclonal antibody blocking VEGF‐α, induced tumor regression in a patient with metastatic ASPS .…”
Section: Assessment Analysis and Discussionmentioning
confidence: 98%
“…A recent phase II study with the tyrosine kinase inhibitor dasatinib included patients diagnosed with chondrosarcoma, who were incurable with conventional therapy. The median PFS for the patients in the study, enrolling all different chondrosarcoma subtypes, was 5.5 months .…”
Section: Discussionmentioning
confidence: 99%